Water sensitivity evaluation of sandstone oil reservoirs with ultra-low permeability. Issue 4 (April 2020) - Liu, X F; Sun, N; Zhao, Z L; Xu, H W; Li, J F; Cao, F; Chen, Z J
Abstract: The development of sandstone reservoirs with ultra-low permeability has become one of the most important energy resources worldwide. Such reservoirs suffer formation damage easily, such as water sensitivity, from foreign fluid during well drilling and completion for extremely poor physical properties. In order to deeply understand the damage degree of water sensitivity of there reservoirs, water sensitivity analysis of Chang 6 reservoir rock samples was carried out, including water sensitivity of block matrix and fracture rock samples. Results show that there are none or weak water sensitivity damage for block matrix while medium water sensitivity damage for fractured samples. The study is of significance to the reservoir damage control in ultra-low permeability oil reservoirs.